Физико-химические основы технологий получения микроэмульсий и полислойных субмикрокристаллических структур сверхпроводников и полупроводников - Кустов, М. В.; Прусский, А. В.; Сидоренко, О. В.; Опалева, Н. С.; Калугин, В. Д.; Бешенцева, О. А. (НТУ "ХПИ", 2010)
Розглянуті фізико-хімічні основи комплексних технологій отримання високоефективних вогнегасних дисперсних систем та електролітичного формування на поверхні металу тонкоплівкових (10² – 10³ нм) покриттів різної хімічної природи з метою отримання мікрошарів надпровідників та напівпровідників (багатокомпонентні металооксидні системи).

Physical and chemical bases of complex technologies of reception highly effective fire extinguisher disperse systems and electrolytic formations on a spending metal constructional basis thin film (10² – 10³ nm) metals of the various nature with the purpose of reception (a method thermoannealing in various gas environments) microlayers of superconductors (intermetallic) or semiconductors (multicomponent metal-oxide systems) are stated.
Keywords: формирования микроструктур; наноструктура; МС; НС; микрослой сверхпроводника; дисперсная фаза; газовый пожарный извещатель; газосигнализатор